PENGARUH STRATEGI PENGEMBANGAN DI INSTALASI FARMASI RUMAH SAKIT DENGAN METODE SWOT (STUDI LITERATUR) - Zulfa Ismaniar Fauzi; Jhonson P Sihombing; Ahmad Purnawarman Faisal; Indah Permata Sari Laia (Poltekkes Kemenkes Medan, 2022)
Pharmacy installations play an important role so that quality health services can be provided in hospitals. To improve these health services, a hospital development strategy is needed. SWOT analysis is an analysis in determining strategy, acting as a tool to minimize existing weaknesses and reduce the impact of threats that arise and must be faced. The purpose of this study was to determine the effect of the pharmaceutical installation development strategy on human resources in hospitals using the SWOT method. This research is a descriptive study conducted in the form of a literature study. This research stage begins by collecting, analyzing and interpreting data while data is obtained from journals that discuss SWOT analysis in hospital pharmacy installations. The following are the results of the research obtained: in literature I, it is known that development strategies affect HR, they have behaved professionally by providing information, education, and counseling services well; in literature II, it was found that there was an influence of development strategies on human resources, making them experienced and skilled but communication with patients was still quite low; while in literature III, the development strategy has an effect on human resources, but there are still weaknesses in the field of communication and direct service to patients. This study concludes that the development strategy has an effect on HR, in literature I it has been carried out well, while in literature II and literature III it has not been carried out well, in terms of service quality and communication with patients.